Stimulation of respiratory activity of Shigella sonnei by certain nitrogenous compounds - Nakamura, Mitsuru (1962)
Nicotinic acid, nicotinamide, tryptophan, pyridine-3-sulfonic acid, aspartic acid, thiamin, glutamic acid, and asparagine stimulated the respiratory activity of Shigella sonnei.